HUBUNGAN KEIKUTSERTAAN KELAS IBU HAMIL DENGAN PENGETAHUAN TENTANG PRE EKLAMPSIA - Suryandari, Artathi Eka; Trisnawati, Yuli (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
Classes for pregnant women are a means to learn together about health for pregnant women, in the form of face-to-face aimed at increasing the knowledge and skills of mothers regarding pregnancy, childbirth, postnatal care and newborns. Danger signs in pregnancy including pre-eclampsia as one of the main causes of maternal death are given through counseling in the class of pregnant women. This study aims to determine the relationship between the participation of pregnant women at classes for pregnant women with knowledge about pre-eclampsia. This type of research is descriptive with the approach of cross-sectional data collection time. The sampling technique is incidental sampling. The study population was all pregnant women in the KarangKlesem sub-district working area of â€‹â€‹South Purwokerto Health Center. The number of samples in this study were 30 respondents. The results showed that there was a significant relationship between the participation of pregnant women and knowledge about pre-eclampsia with Ï value 0,000. Keywords: classes for pregnant women, knowledge, pre eclampsia